Novel nanofabricated dura substitute effectively repairs dural defects independent of defect size in a canine duraplasty model - Matthew R. MacEwan, PhD; Tamas Kovacs, MS; Wilson Z. Ray, MD (Interdisciplinary Neurosurgery, 2018)
Dural substitutes are commonly utilized to repair dural defects incurred during routine neurosurgical procedures. The present study aims to examine whether the resorption rate of a novel non-biologic, fully-resorbable nanofabricated dura substitute is suitable for effective repair of large dural defects.Small or large dural defects were created bilaterally in a canine duraplasty model and then repaired with the nanofabricated dura substitute. Animals were monitored post-operatively for signs of cerebral spinal fluid (CSF) leak and neurological abnormalities. Repair sites were explanted 4 or 13 weeks after surgery and evaluated by histopathology to assess neoduralization, implant resorption, and local inflammation.The nanofabricated dura substitute was observed to prevent CSF leakage and infection. Histopathology confirmed that the gradual resorption of the graft was balanced by increasing neoduralization over time and revealed comparable neoduralization and vascularization between small and large defects both 4 and 13 weeks after surgery. By week 13 all defects were healed with complete neoduralization across the implant site.The nanofabricated dura substitute demonstrated an optimal time course of resorption suited for repair of both large and small dural defects. The present study demonstrates the ability of the nanofabricated dura substitute to regenerate pristine dura in variable size defects. Keywords: Animal model, Nanofabricated dura substitute, Histology